Perilaku Petani Terhadap Program Pemberdayaan dan Pengembangan Usaha Agribisnis Peternakan - GEDE AGUS NEVO HANDRIYANTA; I WAYAN SUDARTA; I DEWA PUTU OKA SUARDI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT Farmers' Behavior on the Empowerment and Development of Animal Agribusiness The Empowerment and Development of Agribusiness at Lembaga Mandiri yang Mengakar di Masyarakat (LM3) is a government program to make agriculture resilient, increasing added value and competitiveness of products, and improving the welfare of farmers. This study aims to assess the behavior of farmers towards the empowerment and development of agribusiness farms in LM3. The location of the study is determined by using purposive and retrieval methods performed by the method of census respondents. Measurement data using a Likert scale and tabulated based on predetermined criteria. Further data analysis descriptive. By using descriptive analysis, it was found that the farmers behavior of the program in the category of middle, by achieving a score of 54.61%. This is due to a lack of seriousness of both parties in implementing program. Therefore, it is suggested that the monitoring of each month from the Department of Animal Husbandry and sustainable development of the program. Keyword: the empowerment, development, agribusiness, behavior.